2022
DOI: 10.1088/1755-1315/1043/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of soils contaminated with oil with a biological product with immobilization of bacteria by carriers from local soils

Abstract: The article shows the effectiveness of the biological product "SHER" developed by "Scientific Industrial Enterprise" AltaiAgroFarm Ltd "(Kazakhstan) on a carrier in the form of screening from local wastes of limestone-shell rock in the process of cleaning soils from oil with a high paraffin content. The results of NGS-sequencing of the consortium of microorganism as part of the probiotic biological product "SHER" established a microbiome of the following type: at the class level 96.15% of all representatives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Table 4 shows the physico-mechanical characteristics of the obtained samples of modified bitumen with an SBS modifier and oil extracted from oil sludge. The ratio of bitumen:sludge:modifier and bitumen:oil:modifier was chosen depending on the type of modifier and characteristics of bitumen, as well as previously studied works [25].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 4 shows the physico-mechanical characteristics of the obtained samples of modified bitumen with an SBS modifier and oil extracted from oil sludge. The ratio of bitumen:sludge:modifier and bitumen:oil:modifier was chosen depending on the type of modifier and characteristics of bitumen, as well as previously studied works [25].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the experiment on remediation of soils contaminated with paraffin oil using a biological preparation at room temperature showed that at 21 °C, the destruction of oil in 3 days was 88.63 % [25], therefore, the separation of the oil-water emulsion was carried out after 24 hours of settling.…”
Section: Table 1 Physico-chemical Characteristics Of Osmentioning
confidence: 99%
See 2 more Smart Citations